Genital self-sampling for HPV-based cervical cancer screening: a qualitative study of preferences and barriers in rural Ethiopia - Lemcke-Brandt, Theresa; Jede, Felix; Knebel Doeberitz, Magnus von; Bussmann, Hermann (BMC public health, 2019)
In the context of WHO’s “task shifting” project and growing global consensus on primary HPV-based cervical cancer screening, self-sampling is a promising new tool to expand screening access, uptake and coverage for women worldwide. We aimed to explore perceptions and acceptability of HPV self-sampling-based cervical cancer screening among community members and health professionals in rural northwest Ethiopia and to identify preferences and socio-cultural barriers regarding self-sampling in order to design a suitable high-coverage screening intervention for a rural African setting.
Gesehen am 19.09.2019